Beauty basics - Lorraine Nordmann (Berkley Books, 1993)
Lorraine Nordmann's Beauty Basics remains the most comprehensive introduction available to therapists at the start of their beauty therapy careers. Carefully mapped to the national occupational standards for beauty therapy at level 1, each chapter relates clearly to the unit it covers, so you can be confident that Beauty Basics will tell you everything you need to know. As a beauty therapist and lecturer with many years' experience, Lorraine Nordmann understands the demands of beauty therapy training at the start of your career, and provides easy-to-follow instructions and guidance. Packed full of full-colour, step-by-step photograph sequences to illustrate key techniques, Beauty Basics will really help you get to grips with the essentials and act as a good point of reference in the salon. From the up-to-the-minute stylish design to the friendly and accessible writing style, this book really does have it all. Endorsed by both the Hair and Beauty Industry Authority (Habia) and City & Guilds, Beauty Basics will give you the head-start you need to go on to become a successful beauty therapist.